2014
DOI: 10.1016/j.pmrj.2014.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Falls, Fear of Falling, Self‐Reported Impairments, and Walking Limitations in Persons With Late Effects of Polio

Abstract: Falls are common in people with mild to moderate late effects of polio, especially later in the day and while walking outdoors. Fear of falling, self-reported impairments, and walking limitations were greater among the persons who fell than in the persons who did not fall. To reduce falls and fear of falling in persons with late effects of polio and to increase their activity level and participation in various life situations, evidence-based interdisciplinary fall management programs are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
72
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 40 publications
(87 citation statements)
references
References 41 publications
13
72
1
1
Order By: Relevance
“…A higher score indicates that the participant is more concerned about falling. FES-I has been shown to have good psychometric properties (Yardley, Beyer, Hauer et al, 2005) and is commonly used to assess fear of falling in elderly, and in persons with different neurological diseases (Bladh, Nilsson, Carlsson, & Lexell, 2013;Blennerhassett, Dite, Ramage, & Richmond, 2012;Brogardh & Lexell, 2014;Moore et al, 2011).…”
Section: Falls Efficacy Scale -International (Fes-i)mentioning
confidence: 99%
See 1 more Smart Citation
“…A higher score indicates that the participant is more concerned about falling. FES-I has been shown to have good psychometric properties (Yardley, Beyer, Hauer et al, 2005) and is commonly used to assess fear of falling in elderly, and in persons with different neurological diseases (Bladh, Nilsson, Carlsson, & Lexell, 2013;Blennerhassett, Dite, Ramage, & Richmond, 2012;Brogardh & Lexell, 2014;Moore et al, 2011).…”
Section: Falls Efficacy Scale -International (Fes-i)mentioning
confidence: 99%
“…Muscle weakness in the lower limbs can lead to limitations in walking ability (Horemans, Bussmann, Beelen, Stam, & Nollet, 2005) and an increased risk of falls (Lord, Allen, Williams, & Gandevia, 2002). Nearly 95% of people with late effects of polio report fear of falling (Brogardh & Lexell, 2014;Legters, Verbus, Kitchen, Tomecsko, & Urban, 2006), and approximately 50% to 84% report falling one or more times per year (Bickerstaffe, Beelen & Nollet, 2010;Brogardh & Lexell, 2014;Silver & Aiello, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Other investigators have reported that 50% to 84% of individuals with PPS admit to falling in the past year (Brogårdh and Lexell, 2014;Hill and Stinson, 2004;Legters et al, 2006;Silver and Aiello, 2002) with 63% to 95% reporting a fear of falling when explicitly asked (Bickerstaffe, Beelen, and Nollet, 2010;Legters et al, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…The neurologic effects from the original polio illness and the later symptoms of PPS, such as increased muscle weakness, fatigue, reduced balance, and walking limitations, contribute to an increased number of risk factors for falls in polio survivors (Bickerstaffe, Beelen, and Nollet, 2010;Brogårdh and Lexell, 2014;Gênet et al, 2009;Hurmuzlu, Basdogan, and Stoianovici, 1996;Legters et al, 2006;Lord, Allen, Williams, and Gandevia, 2002;Silver and Aiello, 2002), thus leading to an increased incidence of falls. The risk factors for falls in older adults, in general, include the following: the use of four or more medications; balance or gait instability; postural hypotension; vision impairment; and home hazards (Bradley, 2011;Weber, White, and McIlvried, 2008;Zeimer, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation